PENGARUH HYBRID SERVICE QUALITY DAN BRAND IMAGE TERHADAP KEPUASAN PELANGGAN - Yudi Kurnia; Ade Octavia (DIGEST MARKETING, 2018)
This study aims to analyze the influence of hybrid service quality and brand image on customer satisfaction simultaneously as well as partially. Sample size consists of 150 units which chosen randomly from customer list transaction. Data analysis used Multiple Regression tools. The results showed that hybrid service quality and brand image simultaneously and partially affects customer satisfaction. Hence, firms suggested to improve service package and developed it whichh is based on simple technology, delivery system and consumer need. Furthermore, satisfaction could build loyalty as an asset to compete.